To add or not to add: The use of quenching agents for the analysis of disinfection by-products in water samples - Kristiana, Ina; Lethorn, A.; Joll, Cynthia; Heitz, Anna (Elsevier Ltd, 2014)
The formation of disinfection by-products (DBPs) is a public health concern due to their potential adverse health effects. Robust and sensitive methods for the analysis of DBPs, as well as appropriate sample handling procedures, are essential to obtain accurate, precise and reliable data on DBP occurrence and formation. In particular, the use of an appropriate quenching agent is critical to prevent further formation of DBPs during the holding time between sample collection and analysis. Despite reports of decomposition of DBPs caused by some quenching agents, particularly sulphite and thiosulphate, a survey of the literature shows that they are still the most commonly used quenching agents in analysis of DBPs.This study investigated the effects of five quenching agents (sodium sulphite, sodium arsenite, sodium borohydride, ascorbic acid, and ammonium chloride) on the stability of seven different classes of DBPs commonly found in drinking waters, in order to determine the most appropriate quenching agent for the different classes of DBPs. All of the quenching agents tested did not adversely affect the concentrations of trihalomethanes (THMs) and haloacetic acids (HAAs), and thus are suitable for quenching of disinfectant residual prior to analysis of these DBPs. Ascorbic acid was found to be suitable for the analysis of haloacetonitriles (HANs) and haloketones (HKs), but should not be used for the analysis of chlorite. Sodium arsenite, sodium borohydride, and ascorbic acid were all acceptable for the analysis of haloacetaldehydes (HALs). All of the quenching agents tested adversely affected the concentration of chloropicrin. A ‘universal’ quenching agent, suitable for all groups of DBPs studied, was not identified. However, based on the results of this study, we recommend the use of ascorbic acid for quenching of samples to be analysed for organic DBPs (i.e. THMs, HAAs, HANs, HKs, and HALs) and sodium sulphite for analysis of inorganic DBPs. Our study is the first comprehensive study on the effects of quenching agents on the stability of DBPs involving a wide range of DBP classes and quenching agents.